Students' Profile Based On Their Learning Style And Its Implication In English Teaching: A Study At SMA MTA Surakarta - Nurjannah, Wahyu Purwati; , Prof. Dr. Endang Fauziati, M. Hum; , Mauly Halwat Hikmat, Ph. D (2014)
This research focuses on the case of the student's profile based on their learning style and its implication in English teaching in SMA MTA Surakarta. The research is aimed to find out: 1) the students' profile of SMA MTA Surakarta, 2) the students' learning style, 3) the major type of learning style used by the students, 4) the students' preferences of learning style, 5) the teaching technique suitable with the learning style. The topic of this research is learning style and the object is the students' learning style. The type of this research is descriptive qualitative research. The data source of this research is the students in X MIA 6 of SMA MTA Surakarta. The data collecting technique is by using questionnaire. There are two sessions in collecting data, in first session the writer uses closedended questionnaire and the second session she uses open-ended questionnaire. The writer uses Fleming's concept of learning style as the theoretical framework to identify the students' learning style in X MIA 6 of SMA MTA Surakarta. From data analysis, the results of this research are: 1) the students' learning styles found are: auditory, read or write and kinesthetic, 2) the major type of learning style is auditory which is used by 27 students in the class (81, 82%), 3) three kinds of the students' preferences of their learning style. The first is auditory preference, they are: often pay attention to the explanation, tend to have discussion, and like listening. The second is read or write preferences, they are: like writing and reading, do not like listening, and like to open dictionary. The third is kinesthetic preferences, they are: tend to write or draw something while listening the presentation, and prefer to have a moving class, 4) the suitable teaching techniques with their learning style such as presentation with practicing something, listening that combined with writing, moving class and discussion. The pedagogical implications of this research are: deciding the teaching techniques which focus on the major type of learning style or focus on one only learning style, then the teacher can combine the teaching techniques which can cover up all the students' learning style.